Farmers' willingness to pay for digital and conventional credit: Insight from a discrete choice experiment in Madagascar. - Yaw Sarfo (Public Library of Science (PLoS), 2021)
In recent decades, microfinance institutions with financial products designed for low income groups have been established all over the world. However, credit access for farmers in developing countries remains low. Digital financial services are rapidly expanding globally at the moment. They also bear great potential to address the credit needs of farmers in remote rural areas. Beyond mobile money services, digital credit is successively offered and also discussed in literature. Compared to conventional credit which is granted based on a thorough assessment of the loan applicant's financial situation, digital credit is granted based on an automated analysis of the existing data of the loan applicant. Despite the potential of digital credit for serving the credit needs of rural farmers, empirical research on farmers' willingness to pay for digital credit is non-existent. We employ a discrete choice experiment to compare farmers' willingness to pay for digital and conventional credit. We apply loan attributes which reflect typical characteristics of both credit products. Our results indicate a higher willingness to pay for digital credit compared to conventional credit. Furthermore, we find that the proximity to withdraw borrowed money has a higher effect on farmers' willingness to pay for digital credit compared to conventional credit. Furthermore, our results show that instalment repayment condition reduces farmers' willingness to pay for digital credit whilst increasing their willingness to pay for conventional credit. Additionally, we find that longer loan duration has a higher effect on farmers' willingness to pay for digital credit compared to conventional credit whereas higher additional credit cost has a lower effect on farmers' willingness to pay for conventional credit compared to digital credit. Our results highlight the potential of digital credit for agricultural finance in rural areas of Madagascar if a certain level of innovation is applied in designing digital credit products.